Hydrolysis Of Starch Below Gelatinization Temperature Using An Amylolytic Enzyme - Utra, Uthumporn (2010)
The action of amylolytic enzymes (α-amylase and glucoamylase) for their ability to hydrolyze starch in native granular state (below gelatinization temperature) and the effect of molecular organization and fine structure of starch polymers on the extent of hydrolysis had been studied. Hydrolysis of raw starches below gelatinization temperature was studied in order to understand the action of the enzyme during hydrolysis. Starches from different botanical origin (corn, mung bean, sago and potato) were chosen and hydrolysis was carried out at 35°C for 24 hours. Then, the susceptibility of cereal starches with different amylose: amylopectin ratios (normal corn, waxy corn, high amylose corn, rice and waxy rice) towards hydrolysis were evaluated in order to establish a correlation between physicochemical and molecular structure of starch. Wheat starch (large and small granules) was hydrolyzed as to evaluate the effect of granule size on the rate and extent of hydrolysis. Starches were also pre-treated with various pre-treatment before subjected to hydrolysis in order to give maximum conversion of starch to fermentable sugars. The effect of heat treatment (50C for 30 minutes) on the susceptibility of corn, mung bean, sago and potato starches towards enzymatic hydrolysis was investigated. Then, the effects of removing lipid and protein (surface/indigenous) of cereal starches on the extent of hydrolysis were studied. Starches were defatted (75% aqueous n-propanol for 7 hours) and protein in starches was removed by treating the starches with NaOH (0.1%) and protease treatment (0.3% w/v).